The Scope of Pesantren Area In The Perspective of Nusantara Islamic Architecture - Mubarok, Jalaluddin; Suprapti, Atiek; Sardjono, Agung Budi (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
Pesantren is an education that is still very typical in Indonesia. Space in architecture is closely related to the activities that arise in a community organization. One of them is within the scope of pesantren. In pesantren has core elements in it. Pesantren studies on architecture are very minimal, so this research develops how the urgency of architectural research on a regional scale, as well as on a micro scale in more important aspects and the sustainability of research that has been carried out. With the literature review method, it will later see the previous research process, which can then be abstracted again in the course of new research on architectural aspects in Pesantren. The result of the related discussion of this review literature is to see the research journey and combine the urgency of Islamic boarding school research and architecture.